Sociological determinants of public perception of transplantology and cloning: gender and age differences - E. A. Smirnova (Vestnik Universiteta, 2026)
Today, human organ and tissue transplantation is developing. In 2023, 3,057 operations were performed in Russia, which is 19.6% more than in 2022. The procedure for providing this type of care is determined by the Federal Laws “On Public Health Protection” and “On Transplantation of Human Organs and (or) Tissues.” The legislator defines the transplantation of human organs and tissues as an extreme method in saving human life. However, doctors and lawyers identify among the main problems: the retribution and injustice of the distribution of donor organs; ethical issues arising during the organ harvesting procedure; determining the moment of death of a deceased donor and the time of termination of resuscitation; the possibility of using organs, tissues and cells of human embryos. In the current circumstances, the relevance of studying the opinion of the population about the medical technology of human organ and tissue transplantation, which has become the purpose of this study, is beyond doubt. According to the study, men and women, regardless of age, agree on the use of therapeutic methods based on organ transplantation. In most cases, they either give neutral assessments (40.9 %) or don’t know anything about it at all (38.8 %).